Pendampingan dan Pemberdayaan UMKM Kopi melalui Penguatan Branding dan Manajemen Keuangan Sederhana di Desa Cane Toa - Mawarni Mawarni; Fairus Fairus; Intan Sari (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Local coffee micro, small, and medium enterprises (MSMEs) in Cane Toa Village face several challenges, including the absence of a clear brand identity, limited financial management practices, and inadequate marketing strategies, which hinder their competitiveness and business sustainability. This community service activity aimed to strengthen the capacity of these local coffee MSMEs by enhancing business branding, providing guidance on simple financial record-keeping, and introducing basic product marketing strategies. The program employed a participatory approach, actively involving MSME actors as key partners throughout all stages, using interactive lectures, focused discussions, and hands-on practice. Implementation was carried out in three main stages: preparation and planning, implementation, and monitoring and evaluation, integrated with the student Community Service Program (KKN). The results demonstrated measurable improvements in participants’ competencies: all participants (100%) successfully developed basic branding elements including business names and simple logos, approximately 85% were able to independently maintain daily financial transaction records, and several participants began to apply structured product marketing strategies. Overall, the program effectively enhanced the professionalism and managerial capacity of local coffee businesses, contributed to economic self-reliance within the Cane Toa Village community, and provided a foundation for sustainable business development, although continued mentoring and institutional support are recommended to maintain long-term outcomes.